Desentralisasi Manajemen Sarana Prasarana - Wangi Dema Lestari; Anne Effane (KARIMAH TAUHID, 2023)
AbstractTo achieve national education goals, the effort that can be made is to provide educational services to students to develop their potential, one of which is by providing adequate facilities and infrastructure. The field of facilities and infrastructure is an aspect that needs to be considered in the implementation of SBM, the procurement of which is the authority and responsibility of schools, SBM is defined as internal control of decision making from the central to school level, planning for infrastructure development begins with needs analysis and mapping implementation, selecting the main needs and developing training specifications, the implementation of the construction of infrastructure facilities is carried out with the support of the school board, parents and councils, supervision of the development of infrastructure facilities is carried out through direct and indirect access. There are several limitations to the development of facilities and infrastructure. The involvement of entrepreneurs in educational settings is not evenly distributed, the leadership abilities of the school committee, the qualifications of parents are unequal. Student involvement in the process of maintaining facilities is still low. School infrastructure, efforts to break down barriers. Development of infrastructure facilities, namely personal training, quality improvement. Lead, build and maintain the initial involvement of parents and prospective students. Collaboration with other schools/agencies.